Primary Ewing’s sarcoma of the intestine: case report and literature review - Luo, Baofa; Gao, Wei; Li, Ting; Yu, Xinran; Guo, Fei (Frontiers in Oncology, 2024)
Ewing sarcoma (ES)/peripheral primitive neuroectodermal tumor is a highly aggressive malignant tumor that typically presents in bone and soft tissue. Primary ES of the intestine is relatively rare, which poses a challenge in distinguishing it from other primary tumors of the small intestine through imaging. This article details a case study of ES originating in the intestine. Computed tomography (CT) imaging suggested a small intestinal stromal tumor, and so the patient underwent resection of the small bowel and omental tumor. Pathology results confirmed the diagnosis of ES of the small intestine. Following surgery, the patient underwent six cycles of chemotherapy, and a follow-up positron emission tomography–CT revealed widespread dissemination of the disease with intraperitoneal metastasis, ultimately resulting in the death of the patient.